Eating Behaviors and Dietary Changes in Patients With Dementia. (December 2016) - Cipriani, Gabriele; Carlesi, Cecilia; Lucetti, Claudio; Danti, Sabrina; Nuti, Angelo
Background: Eating problems and dietary changes have been reported in patients with dementia. Objectives: The aim of this article is to explore the generalized problems with nutrition, diet, feeding, and eating reported among patients with dementia. Methods: Medline and Google Scholar searches were conducted for relevant articles, chapters, and books published before 2016. Search terms used included behavioral and psychological symptoms of dementia, dementia, dietary changes, eating behavior. Publications found through this indexed search were reviewed for further relevant references. Results: Abnormal eating behaviors, eating problems, and dietary changes are present in most people with dementia, especially in the later stages of the condition. Conclusion: Individuals with dementia frequently develop serious feeding difficulties and changes in eating and dietary habits. The changes may be secondary to cognitive impairment or apraxia, or the result of insufficient caregiving, or the consequence of metabolic or neurochemical abnormalities occurring as part of the dementing process.